2013
DOI: 10.19090/pp.2013.4.371-383
|View full text |Cite
|
Sign up to set email alerts
|

Dinamičko procenjivanje zone narednog razvoja testom za ispitivanje prvaka-1 (TIP-1)

Abstract: Osnovni predmet rada jeste ispitivanje mogućnosti primene instrumenta TIP-1 za dinamičko procenjivanje zone narednog razvoja. U okviru istraživanja su za svako dete dobijeni podaci o zoni aktuelnog razvoja (ZAR) i, uz odgovarajuće modifikacije procedure ispitivanja, o zoni narednog razvoja (ZNR). Rezultati pokazuju da su ZAR i ZNR u pozitivnoj korelaciji (r = .50), što je veća ZAR veća je i ZNR i obrnuto, što je slabije samostalno postignuće u manjoj meri dete napreduje i u saradnji sa kompetentnijim od… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
1
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
2
1
0
1
Order By: Relevance
“…They made a significant improvement and achieved on average a result that was three times higher than the one from their first independent attempt. This kind of finding was also expected and in line with the previous studies on the improvement of children from disadvantaged backgrounds within AI (Sternberg & Grigorenko, 2002;Luković, 2011;Luković et al, 2013;Chaffey et al, 2003). In addition, the quantitative analysis did not single out one type of scaffolding that had the most significant influence on the children's improvement.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…They made a significant improvement and achieved on average a result that was three times higher than the one from their first independent attempt. This kind of finding was also expected and in line with the previous studies on the improvement of children from disadvantaged backgrounds within AI (Sternberg & Grigorenko, 2002;Luković, 2011;Luković et al, 2013;Chaffey et al, 2003). In addition, the quantitative analysis did not single out one type of scaffolding that had the most significant influence on the children's improvement.…”
Section: Discussionsupporting
confidence: 84%
“…A study by Stenberg and Grigorenko (Sternberg & Grigorenko, 2002) analyzed test approaches based on the notion of the zone of proximal development and showed that children from culturally and educationally deprived environments improved significantly when solving tasks in AI compared to their achievement when solving tasks independently. Similar data were obtained in a research involving preschoolers with low TIP1 test achievement since they also improved significantly during dynamic assessment (Luković, 2011;Luković et al, 2013). Its analysis showed that the preschoolers involved in the research came from poor families and communities, that they were not enrolled in a preschool program and that their parents did not have the capacity to provide conditions which would meet developmental needs of their children.…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…Uvažavajući ovaj koncept zone narednog razvoja, neki autori predlažu uvođenje dinamičke procene [11]. Predlog je u potpunosti u skladu sa idejom inkluzivnog obrazovanja, ali se s obzirom da trenutnu organizaciju obrazovnog sistema, još uvek čini nedostižnim.…”
Section: Promena Paradigmeunclassified